Understanding the imaginary war : culture, thought and nuclear conflict, 1945-90 - Grant, Matthew, 1980-; Ziemann, Benjamin (Cultural history of modern war., 2016)
Presents a comparative overview of the cultural imaginations of nuclear weapons and the anticipation of nuclear destruction. It considers representations of elements of the Cold War in popular culture and thought across Europe, Japan, USSR and the USA, providing a significant addition to Cold War historiography.